The EU claims that there has been sufficient progress in the EPA negotiations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
According to an EU press release the ACP-EU Council of Ministers took note of...